Managing conflict-generating invasive species in South Africa: Challenges and trade-offs - Zengeya, Tsungai; Ivey, Philip; Woodford, Darragh J.; Weyl, Olaf; Novoa, Ana; Shackleton, Ross; Richardson, David; van Wilgen, Brian (African Biodiversity & Conservation, 2017)
Background: This paper reviewed the benefits and negative impacts of alien species that are currently listed in the Alien and Invasive Species Regulations of the National Environmental Management: Biodiversity Act (Act no 10 of 2004) and certain alien species that are not yet listed in the regulations for which conflicts of interest complicate management. Objectives: Specifically, it identified conflict-generating species, evaluated the causes and driving forces of these conflicts and assessed how the conflicts have affected management. Method: A simple scoring system was used to classify the alien species according to their relative degree of benefits and negative impacts. Conflict-generating species were then identified and further evaluated using an integrated cognitive hierarchy theory and risk perception framework to identify the value systems (intrinsic and economic) and risk perceptions associated with each conflict. Results: A total of 552 alien species were assessed. Most of the species were classified as inconsequential (55%) or destructive (29%). Beneficial (10%) and conflict-generating (6%) species made a minor contribution. The majority (46%) of the conflict cases were associated with more than one value system or both values and risk perception. The other conflicts cases were based on intrinsic (40%) and utilitarian (14%) value systems. Conclusions: Conflicts based on value and risk perceptions are inherently difficult to resolve because authorities need to balance the needs of different stakeholders while meeting the mandate of conserving the environment, ecosystem services and human well-being. This paper uses the identified conflict-generating